Influence of stone content on face stability for tunnels in sandy cobble strata - Xue, Haifang; Wang, Haoteng; Li, Lingyun; Gong, Xiaoqin; Zhao, Ying; Zhao, Jianbin; Zhang, Yonghao (Frontiers in Earth Science, 2023)
As a result of the complex geological conditions of sand-cobble stratum, various types of problems may arise during construction of tunnels crossing sand-cobble stratum, the most prominent of which is the stability problem of the face. In order to study the stability of the tunnel face in sand-cobble stratum, first, a continuous medium model of sandstone soil is established, and numerical simulation is carried out on the three-axis compression test of sandstone soil to analyze its micro-mechanical characteristics. Second, a calculation model of simulated sandstone strata excavation is established by FLAC3D finite difference software. Then, the safety factor K calculated by the strength reduction method is introduced as the evaluation index of the face stability, and the face stability of sand-cobble tunnels with a series of stone content, tunnel burial depth and tunnel diameter are analyzed. The results show that the macro stress-strain curve of sand-cobble soil in the three-axis compression test can be divided into linear stage, elastic-plastic stage and ideal plastic stage, and the shear strength of sand-cobble soil increases with the increase of stone content. In the process of tunnel excavation, the stability of tunnel face increases with the increase of stone content in the stratum; while the tunnel buried depth and diameter increase, the stability of tunnel face decreases. These results provide a reference for predicting the instability and failure of sand-cobble tunnels, which is critical for the construction and safety of tunnels in sand-cobble stratum.